Draft Annual Plan 1987-88 Volume : IV General Areas Government of Assam - Planning Commission (Planning Commission, 1987)
Out of the total proposed outlay of Rs. 2820.00 lakhs for 1987-88 for General Areas, the proposed flow for Tribal Areas is Rs.479.40 lakhs. This amount will be utilised in Tribal Areas for divisible schemes i.e. Metaling and Blacktopping, Improvement of Low Standard Roads, RMNP and other than RMNP. The work will be taken up as mentioned above against the schematic Subheads concerned.
Government of Assam, Planning and Development Department